2007
DOI: 10.1007/s10531-007-9271-6
|View full text |Cite
|
Sign up to set email alerts
|

Coral community structure and risk assessment of high-latitude reefs at Sodwana Bay, South Africa

Abstract: The importance of studying coral communities at different spatial scales is acknowledged in a growing volume of scientific literature, and principles of landscape ecology were thus used to elucidate the patterns in coral community structure on the highlatitude reefs in South Africa. These reefs are at the southernmost distribution of this fauna in Africa, are surprisingly species rich, and represent a biodiversity peak in this fauna south of the equator, regardless of the marginal nature of the environment. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 35 publications
1
23
0
Order By: Relevance
“…Estimates of hard coral cover (as a percentage of total benthic cover) on Sodwana reefs vary considerably. Riegl et al (1995) and Riegl and Riegl (1996) reported values around 22.5% for Two-Mile Reef, Schleyer et al (2008) reported averages around 10-12% at Nine-Mile Reef and Celliers and Schleyer (2008) reported values of 29% for Two-Mile Reef. Our value of 48.4% is consequently very high, but similar to that of 48.8% reported for Four-Mile Reef by Celliers and Schleyer (2008).…”
Section: Composition Of Hard Substratamentioning
confidence: 98%
See 3 more Smart Citations
“…Estimates of hard coral cover (as a percentage of total benthic cover) on Sodwana reefs vary considerably. Riegl et al (1995) and Riegl and Riegl (1996) reported values around 22.5% for Two-Mile Reef, Schleyer et al (2008) reported averages around 10-12% at Nine-Mile Reef and Celliers and Schleyer (2008) reported values of 29% for Two-Mile Reef. Our value of 48.4% is consequently very high, but similar to that of 48.8% reported for Four-Mile Reef by Celliers and Schleyer (2008).…”
Section: Composition Of Hard Substratamentioning
confidence: 98%
“…Riegl et al (1995) and Riegl and Riegl (1996) reported values around 22.5% for Two-Mile Reef, Schleyer et al (2008) reported averages around 10-12% at Nine-Mile Reef and Celliers and Schleyer (2008) reported values of 29% for Two-Mile Reef. Our value of 48.4% is consequently very high, but similar to that of 48.8% reported for Four-Mile Reef by Celliers and Schleyer (2008). Although this might indicate that Two-Mile Reef was in good condition at the time we sampled, we suggest that such comparisons should be treated with caution, as differences between methods (point-intercept vs photographic quadrats), total area sampled and sampling site would all affect such data.…”
Section: Composition Of Hard Substratamentioning
confidence: 98%
See 2 more Smart Citations
“…Outcrops are present (Figure 1b,c) and originate from fossilization of Late Pleistocene beaches and dunes [49] that form very flat structures [50]. The area is characterized by high levels of endemic species [51][52][53] with the coral cover being dominated by soft corals that are tolerant to strong wave energy and sediment resuspension [54][55][56][57]. …”
Section: Study Sitementioning
confidence: 99%